Associations between unit workloads and outcomes of first extubation attempts in extremely premature infants below a gestational age of 26 weeks - Ohnstad, Mari Oma; Stensvold, Hans Jørgen; Pripp, Are Hugo; Tvedt, Christine Raaen; Jelsness-Jørgensen, Lars-Petter; Astrup, Henriette; Eriksen, Beate Horsberg; Lunnay, Mai Linn; Mreihil, Khalaf; Pedersen, Tanja; Rettedal, Siren Irene; Selberg, Terje Reidar; et al. (Frontiers in Pediatrics, 2023)
Objective: The objective was to explore whether high workloads in neonatal intensive care units were associated with short-term respiratory outcomes of extremely premature (EP) infants born < 26 weeks of gestational age. Methods: This was a population-based study using data from the Norwegian Neonatal Network supplemented by data extracted from the medical records of EP infants born from 2013–2018. Results: We analyzed 316 first extubation attempts. There were no associations between unit workloads and the duration of mechanical ventilation until each infant’s first extubation or the outcomes of these attempts. Additionally, there were no weekend or seasonal effects on the outcomes explored. Workloads did not affect the causes of reintubation for infants who failed their first extubation attempt. Conclusion: Our finding that there was no association between the organizational factors explored and short-term respiratory outcomes can be interpreted as indicating resilience in Norwegian neonatal intensive care units.